PUBLICATIONS OF THE WEEK. (Bookseller, 2002)
Presents a list of book publications prepared by Whitaker Information Services as of March 29, 2002. Contact Information; Date of publication of the book 'Bad Girls of Pulp Fiction,' by Nancy Armstrong; Autobiographical work presented in Hugh Barrett's 'Good Living.'